HFA‐PEFF score: prognosis in patients with preserved ejection fraction after transcatheter aortic valve implantation. (29th January 2022) - Seoudy, Hatim; von Eberstein, Mira; Frank, Johanne; Thomann, Maren; Puehler, Thomas; Lutter, Georg; Lutz, Matthias; Bramlage, Peter; Frey, Norbert; Saad, Mohammed; Frank, Derk
Abstract: Aims: Many transcatheter aortic valve implantation (TAVI) candidates have underlying heart failure with preserved ejection fraction (HFpEF) in addition to symptomatic aortic stenosis. Diagnosis of HFpEF is challenging. The Heart Failure Association of the European Society of Cardiology proposed the HFA‐PEFF score as part of a novel diagnostic algorithm. This study assessed the prognostic value of the HFA‐PEFF score in patients with preserved ejection fraction after TAVI. Methods and results: This single‐centre study included 570 consecutive TAVI patients with a preserved left ventricular ejection fraction of ≥50%. Patients with an HFA‐PEFF score of ≥5 [ n  = 239 (41.9%)] were compared with those with <5 points [ n  = 331 (58.1%)]. The primary outcome was a composite of all‐cause mortality or first heart failure rehospitalization within 1 year after TAVI. Secondary endpoints were the individual components of the primary outcome. Patients with an HFA‐PEFF score ≥ 5 had higher rates of comorbidities commonly associated with HFpEF, a higher rate of new pacemaker implantation after TAVI, were at increased risk of the primary composite endpoint (25.5% vs. 10.0%, P  < 0.001), and rehospitalization for heart failure (11.7% vs. 3.9%, P  < 0.001). Multivariable analysis confirmed an HFA‐PEFF score ≥ 5 as an independent risk factor for the composite endpoint [hazard ratio 2.70, 95% confidence interval (CI) 1.70–4.28, P  < 0.001] and for all‐cause mortality (hazard ratio 2.58, 95% CI 1.46–4.53, P  = 0.001). Conclusion: The HFA‐PEFF score is associated with all‐cause mortality and heart failure rehospitalization in patients with preserved ejection fraction after TAVI. This practical tool can easily be incorporated into risk stratification algorithms for TAVI patients.